ريادة المهلهل بين الشّكّ واليقين (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
تركت مقولة ابن سلاّم: "المهلهل أوّل من قصّد القصائد" صدىً واسعاً في مؤلّفات من جاء بعده، وقُبلت بوصفها حكماً نقدياً دقيقاً لا مسوّغ لإقامة الدّليل عليه. و ربّما مهّدت للاقتناع بآراء القائلين باشتقاق لقب "المهلهل" من "الهلهلة" التي تعنى ضعفاً في صياغة الشّعر؛ إذ من المألوف أن تفتقر صناعة "الأوّل" إلى الإحكام الذي يُلاحظ في صناعة من يأتي بعده، ويستفيد من تجاربه. ولكنّ الباحث يفترض أنّ الصّورة النّاضجة لمراثي المهلهل، تنمّ على إفادته من تجارب أسلافه، وعلى جريه في ميدان مهّدوه له. وهذا البحث محاولة لاختبار هذا الفرض، والوقوف على حقيقة الدّور الرّيادي المنسوب إلى الشّاعر. Bin Sallam's statement "Muhalhal is the first to compose poems" has met a widespread fame in the publications of those authors coming after him, and has been accepted as a precise critical judgment that attracts no excuse to handle it sharply. It has probably paved the way to accept the vantage point of those who suggest that the title "Muhalhal" is derived from "al-halhalah" which means weakness in poetry composing; since it is quite known that the craft of the "First" necessitates the coherence that appears in the craft of those followers, and benefits from his expertise. However, the researcher presumes that the ripe image of Muhalhal's elegies explains his reliance on his predecessors' expertise, and, as well, his contribution to a field they have established. This piece of research is an attempt to test this presumption, and scrutinize the reality of the pioneering role attributed to this poet.